FLEKSIBILlTAS MUSIKAL SULUKAN GAYA SURAKARTA - Suyoto Suyoto (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2004)
Wayang kulit is a representation of human life since the birth until the death which is presented in patMt (musical concept or musical atmosphere). Sulukan is an important medium and it is the